An 111In-labelled bis-ruthenium(ii) dipyridophenazine theranostic complex: mismatch DNA binding and selective radiotoxicity towards MMR-deficient cancer cells. Issue 33 (14th August 2020) - Gill, Martin R.; Walker, Michael G.; Able, Sarah; Tietz, Ole; Lakshminarayanan, Abirami; Anderson, Rachel; Chalk, Rod; El-Sagheer, Afaf H.; Brown, Tom; Thomas, Jim A.; Vallis, Katherine A.
Abstract : Auger electron emitter indium-111 demonstrates cancer-selective radiotoxicity and SPECT imaging compatibility when conjugated to a ruthenium(ii ) polypyridyl complex. Abstract : Theranostic radionuclides that emit Auger electrons (AE) can generate highly localised DNA damage and the accompanying gamma ray emission can be used for single-photon emission computed tomography (SPECT) imaging. Mismatched DNA base pairs (mismatches) are DNA lesions that are abundant in cells deficient in MMR (mismatch mediated repair) proteins. This form of genetic instability is prevalent in the MMR-deficient subset of colorectal cancers and is a potential target for AE radiotherapeutics. Herein we report the synthesis of a mismatch DNA binding bis-ruthenium(ii ) dipyridophenazine (dppz) complex that can be radiolabelled with the Auger electron emitting radionuclide indium-111 ( 111 In). Greater stabilisation accompanied by enhanced MLCT (metal to ligand charge-transfer) luminescence of both the bis-Ru(dppz) chelator and non-radioactive indium-loaded complex was observed in the presence of a TT mismatch-containing duplex compared to matched DNA. The radioactive construct [ 111 In]In-bisRu(dppz) ([ 111 In][In-2 ] 4+ ) targets cell nuclei and is radiotoxic towards MMR-deficient human colorectal cancer cells showing substantially less detrimental effects in a paired cell line with restored MMR function. Additional cell line studies revealed that [ 111 In][In-2 ] 4+ is preferentially radiotoxic towards MMR-deficient colorectal cancer cells accompanied by increased DNA damage due to 111 In decay. The biodistribution of [ 111 In][In-2 ] 4+ in live mice was demonstrated using SPECT. These results illustrate how a Ru(ii ) polypyridyl complex can incorporate mismatch DNA binding and radiometal chelation in a single molecule, generating a DNA-targeting AE radiopharmaceutical that displays selective radiotoxicity towards MMR-deficient cancer cells and is compatible with whole organism SPECT imaging.